(untitled) (Foro de Educacion, 2014)
In today’s society, carrying out studies abroad is a highly recommended option and increasingly common in academic students, due to the many advantages it brings to their knowledge. However, the obstacles that these students face to (culture shock, language, etc..) may make their stay less fruitful than considered before coming. Based on this fact, this article shows how they have solved this problem, through a reception and accompaniment project for foreign students, at a Pedagogical University in a city in southern Germany. This article describes the project which covers the main needs of international students attending this German University, also showing what is its purpose and which activities and actions promotes this project for the benefit of foreign students and in the context they are developed. The presentation and knowledge of this project can be a great help to create or improve spanish host initiatives. In turn presents the potential that could have the creation of an equivalent initiative in the University of Granada, that would host and guidance to foreign students during their stay, without prejudice to the services offered by this University for the student coming from other countries.